Solar-powered seawater desalination: A contribution to provide energy-efficient clean water - Widjonarko, Widjonarko; Aditya Rahardi, Gamma; Rudiyanto, Bayu; Ishamul Ayady Akma, Ahmad; Ahmed Mohammed Ate, Abdelrahim (Universitas Muhammadiyah Magelang, 2023)
This study focuses on developing a prototype for a seawater desalination system powered by solarpanel. The desalination process is heated by a solar collector and 150 WP solar panel. The primaryobjective is to design, develop, and evaluate the prototype's efficacy, affordability, and scalability.The efficiency was measured by the quantity of freshwater produced per unit of solar energy. Ofthe three distillation tests, it was determined that the addition of a heater enhanced theperformance of the system. However, the overall efficiency was limited due to the solar panel andcollector's low heat output. A positive correlation was observed between irradiance andtemperature, but incomplete evaporation indicated the need for additional research to optimizethe process. The system consisted of a solar collector, a heater, and a distillation apparatus. Threedistillation tests revealed that the addition of a heater improved the system's performance,resulting in a maximum achievable efficiency of 0.99% and the production of 16 ml of fresh water.This study demonstrates the potential for renewable energy sources to power seawaterdesalination and lays the groundwork for future sustainable desalination technologies despite itslimitations.